2017
DOI: 10.1136/bmjopen-2016-013425
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and behavioural patterns of stigma among patients with type 2 diabetes: a cross-sectional study

Abstract: ObjectivesThe aim of this study was to test the psychological and behavioural patterns of stigma (self-esteem and social participation) and their relationship to self-stigma, patient activation for engaging in self-care and glycaemic control among patients with type 2 diabetes mellitus (T2DM).DesignA cross-sectional study.Setting2 tertiary-level hospitals and 2 secondary-level hospitals in Japan.ParticipantsA consecutive sample of 209 outpatients with T2DM. Inclusion criteria were as follows: presence of T2DM,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 27 publications
3
35
0
Order By: Relevance
“…Five studies reported on the prevalence of perceived stigma ranging from 12% to 86% [ 12 , 37 , 60 , 61 , 62 ] and three on experienced stigma ranging from 5.6% to 68.5% [ 30 , 60 , 61 ]. Six studies measured and reported the mean levels/scores of stigma, the range of which varied based on the scale used [ 10 , 12 , 38 , 59 , 63 , 64 ]. Table 3 shows the reported prevalence and/or mean levels/scores of stigma across different NCDs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five studies reported on the prevalence of perceived stigma ranging from 12% to 86% [ 12 , 37 , 60 , 61 , 62 ] and three on experienced stigma ranging from 5.6% to 68.5% [ 30 , 60 , 61 ]. Six studies measured and reported the mean levels/scores of stigma, the range of which varied based on the scale used [ 10 , 12 , 38 , 59 , 63 , 64 ]. Table 3 shows the reported prevalence and/or mean levels/scores of stigma across different NCDs.…”
Section: Resultsmentioning
confidence: 99%
“…The other source of stigma identified in the articles included societal actors who played part in stigmatization as a result of the influence and enforcement of societal norms which discredit and devalue those with health conditions, viz. family [ 8 , 9 , 11 , 28 , 29 , 31 , 32 , 36 , 38 , 59 ], friends [ 9 , 28 , 29 , 31 , 32 , 38 , 59 ], doctors/healthcare providers [ 9 , 28 , 29 , 34 , 38 , 59 ], employers [ 30 , 33 , 62 ], and colleagues at the workplace [ 9 , 38 , 62 ]. Most studies identified and examined the role of family and friends as perpetuators of stigma, followed by healthcare providers, employers, and work colleagues.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the light of this evidence, novel approaches to reduce sedentary behaviours are urgently needed, as well as updated public health recommendations increasing awareness of the risk associated with these behaviours. This is particularly relevant for individuals with T2D, as they are exposed to an increased demand of self-care and, simultaneously, they typically display an increased vulnerability to psychological distress [2,35,36], which, in turn, is associated with poorer clinical outcomes and a higher occurrence of un-healthy behaviours.…”
Section: Introductionmentioning
confidence: 99%